Using the "LEARN Model" to resolve guest complaints - Galičić, Vlado; Ivanović, Slobodan, ekonomist (2008)
Abstract: The demands of guest in the hospitality industry and their satisfaction with the services they have consumed have become a prevailing competitive tool. Today, the guest as an individual is capable of damaging the reputation of a hospitality service provider by telling others of his/her experiences of the shortcoming of services rendered and consumed. Complaints against hospitality establishments are often calls of attention to the need for improving not only the overall process of preparing and rendering service or one of its parts but also the entire way operations are organised in a hospitality facility. What guests really mind and what causes customer-defection is an indolent and negligent attitude of a hospitality establishment towards guest complaints. In principle, complainants do not have a negative view of a specific hospitality facility and most guests do not make formal complaints. Instead, they choose to simply leave a facility when something is not to their liking, never to return, and turn to the competition. The purpose of this paper is to explain how the objections and formally expressed complaints of guests can be transformed into stronger loyalty towards a hospitality facility or specific type of service, because guests who have seen their claims resolved in a satisfactory manner are very likely to tell others of their experience. To this end, the paper focuses on the LEARN Model for resolving guest complaints against hospitality servicesunderstanding of this paper, the following section provides a brief
Bibliografija: 7 jed
Keywords: Hotelijerstvo -- Pritužbe gostiju -- Reklamacije